The process of organization of health in Cuba (1902-1906). TheSanitary Ordinances of 1906 - Sónchez Sónchez, Samuel; Rodríguez Morales, Osvaldo; Sónchez Gólvez, Samuel (Revista Universidad de Guayaquil, 2016)
Between 1898 and 1909, medicine in Cuba underwent a period of profound transformations. The culminating point of that period were the Health Ordinances of 1906, the first Cuban sanitary code. It constituted, until that moment, the biggest attempt to organize the health in the country. It disposed of a technical rigor to the height of the most advanced in the world then. However, tne lack of investigative analytical attention to their content is contradictory. The aim of this paper was to analyze tne main legal provisions regarding Health in the period 1898-1906 as well as the content of the Sanitary Ordinances. Guided by the scientific method, heuristic, historical- logical, inductive-deductive, synthetic analytical methods were used, among others. A total of 12 materials were consulted. Of primary importance were primary sources such as the Sanitary Ordinances, the Acts of the Constituent Assembly of 1901 ana the Military Order. In a conclusive way, beyond their demonstrated values, the fundamental! limitation of the Law on Sanitary Ordinances was based on the decentralized character of the health that it raised, when the Local Health Boards were dependent on the municipal councils.
Keywords: health; Military Order; Sanitary Ordinances; medicine; Cuba